Reliability and validity study of the Finnish version 2.0 of the oswestry disability index - Pekkanen, Liisa; Kautiainen, Hannu; Ylinen, Jari; Salo, Petri; Häkkinen, Arja (Spine (Philadelphia, Pa. 1976), 2011)
Prospective clinical validation study. The aims of this study were to translate into Finnish and culturally adapt and study the psycho-metric properties of the Oswestry Disability Index (ODI) version 2.0. The ODI is one of the most commonly reported back-specific disability questionnaires. It is widely used both in clinical work and in medical studies. To date, no validated Finnish version of the ODI version 2.0 has been reported. The ODI version 2.0 was translated into the Finnish language. A total of 115 patients with back pain, referred by the primary care physician to the outpatient clinic of the department of physical medicine and rehabilitation, were recruited for this study. The patients answered a questionnaire package that included the Finnish ODI 2.0, Back Pain Questionnaire for Visual Analogue Assessment (Million-VAS), Visual Analogue Scales of back and leg pain (VASback, VASleg), the Depressions Scale, and a question on their subjectively perceived health. The package was administered twice; 2 weeks before and at the arrival to the clinic. Reproducibility of the ODI was 0.90 (95% confidence interval [CI] = 0.85-0.94) and the internal consistency was 0.86 (95% CI = 0.81-0.90). Factor analysis showed that the ODI was loaded on 2 factors, which explained 51% of the total variance. In testing convergent validity ODI correlated with Million-VAS, r = 0.75 (95% CI = 0.64-0.84); VASback, r = 0.48 (95% CI = 0.32-0.62); and VAS leg, r = 0.41 (95% CI = 0.23-0.57). The Finnish ODI version 2.0 proved to be a valid and reliable instrument that showed psychometric properties comparable with the original English version. Therefore, it can be used in assessing the disability among Finnish-speaking patients with back pain for both clinical and scientific purposes.